Further insights into the treatment of perineal hernia based on a the experience of a single tertiary centre. (23rd January 2020) - Blok, R. D.; Brouwer, T. P. A.; Sharabiany, S.; Musters, G. D.; Hompes, R.; Bemelman, W. A.; Tanis, P. J.
Abstract: Aim: There is little evidence concerning the optimal surgical technique for the repair of perineal hernia. This study aimed to report on the evolution of a technique for repair of perineal hernia by analysing the experience in a tertiary referral centre. Method: This was a retrospective review of consecutive patients who underwent perineal hernia repair after abdominoperineal excision in a tertiary referral centre. The main study end‐points were rate of recurrent perineal hernia, perineal wound complications and related re‐intervention. Results: Thirty‐four patients were included: in 18 patients a biological mesh was used followed by 16 patients who underwent synthetic mesh repair. Postoperative perineal wound infection occurred in two patients (11%) after biological mesh repair compared with four (25%) after synthetic mesh repair ( P  = 0.387). None of the meshes were explanted. Recurrent perineal hernia following biological mesh was found in 7 of 18 patients (39%) after a median of 33 months. The recurrence rate with a synthetic mesh was 5 of 16 patients (31%) after a median of 17 months ( P  = 0.642). Re‐repair was performed in four (22%) and two patients (13%), respectively ( P  = 0.660). Eight patients required a transposition flap reconstruction to close the perineum over the mesh, and no recurrent hernias were observed in this subgroup ( P  = 0.030). No mesh‐related small bowel complications occurred. Conclusion: Recurrence rates after perineal hernia repair following abdominoperineal excision were high, and did not seem to be related to the type of mesh. If a transposition flap was added to the mesh repair no recurrences were observed, but this finding needs confirmation in larger studies.